First field records of the sexuales (males and oviparae) of Toxoptera aurantii (Hemiptera: Aphididae) - Hidalgo, Nicolás Pérez; Mifsud, David (Zootaxa, 2011)
Toxoptera aurantii (Boyer de Fonscolombe) is an aphid pest of great agricultural importance, not only due to its polyphagy but mostly due to its ability to transmit various plant viruses e.g. Citrus tristeza virus on Citrus (Blackman & Eastop, 2000). Blackman & Eastop (2000) considered this aphid to be entirely anholocyclic, because no sexual morphs have ever been observed in the field.